Total Phenolic Content and Antioxidant Activity of Different Extracts of Aronia melanocarpa L. Fruit - Nurcan Kılıç Baygutalp; Mehmet Şekeroğulları; Lale Duysak (Pharmata)
Objective: Aronia melanocarpa L. (aronia) fruit contains anthocyanins, flavonoids, phenolic acids, and compounds from the polyphenol group. The fruits of this plant are the most abundant natural source of anthocyanins. The aim of this study is to determine the total phenolic compound amount of methanol and ethanol extract in the fruit of the aronia plant and to investigate itsantioxidant effects.Methods: Ethanol and methanol extracts from aronia fruits were obtained. The Folin–Ciocalteu Reagent (FCR) was used to determine the total phenolic component levels in the extracts of aronia. By using the 1,1-diphenyl-2-picrylhydrazyl (DPPH), iron ion reducing antioxidant power (FRAP), and Cu2+ ion reducing (CUPRAC) techniques, antioxidant activities were assessed. To calculate the extracts’ equivalent antioxidant capacity, different reference sample concentrations ranging from 125 to 500 g/mL were prepared.Results: Both ethanol and methanol aronia extracts showed the highest phenolic component at a concentration of 500 µL/mL. Similary, both extracts FRAP and CUPRAC (Trolox Eq g/mL) activities and DPPH radical scavenging capacity (inhibition %) were highest at the concentration of 500 µL/mL.Conclusion: Aronia stands out as an antioxidant fruit and a potential natural therapeutic agents to alleviate oxidative stress. More research is needed to elucidate the exact mechanisms of action, optimum extraction method, optimal dosage, and potential side effects of the extracts.